Actin in erythrocyte ghosts and its association with spectrin. Evidence for a nonfilamentous form of these two molecules in situ (The Rockefeller University Press, 1975)
Actin was isolated from erythrocyte ghosts. It is identical to muscle actin in its molecular weight, net charge, ability to polymerize into filaments with the double helical morphology, and its decoration with heavy meromyosin (HMM). when erythrocyte ghosts are incubated in 0.1 mM EDTA, actin and spectrin are solubilized. Spectrin has a larger molecular weight than muscle myosin. When salt is added to the EDTA extract, a branching filamentous polymer is formed. However, when muscle actin and the EDTA extract are mixed together in the presence of salt, the viscosity achieved is less than the viscosity of the solution if spectrin is omitted. Thus, spectrin seems to inhibit the polymerization of actin. If the actin is already polymerized, the addition of spectrin increases the viscosity of the solution, presumably by cross-linking the actin filaments. The addition of HMM of trypsin to erythrocyte ghosts results in filament formation in situ. These agents apparently act by detaching erythrocyte actin from spectrin, thereby allowing the polmerization of one or both proteins to occur. Since filaments are not present in untreated erythrocyte ghosts, we conclude that erythrocyte actin and spectrin associate to form an anastomosing network beneath the erythrocyte membrane. This network presumably functions in restricting the lateral movement of membrane-penetrating particles.